SEASONAL CHANGES IN STABLE CARBON ISOTOPIC COMPOSITION OF N-ALKANES IN THE MARINE AEROSOLS FROM THE WESTERN NORTH PACIFIC: IMPLICATIONS FOR THE SOURCE AND ATMOSPHERIC TRANSPORT - Bendle J.A.; Kawamura K.; Yamazaki K. (My University, 2006)
To constrain seasonal changes in the long-range atmospheric transport of land-derived lipid biomarker compounds, we investigated the compound-specific stable isotopic composition of marine aerosol n-alkanes collected from 1990 to 1993 at a remote island, Chichi-Jima (27?04?N, 142?13?E), in the western North Pacific. Compound-specific isotope analysis revealed, in particular, strong seasonal changes in the ?13C values of the C29 and C31 n-alkanes (biomarkers for higher plants). Lighter ?13C values were observed in winter (typically -32 to -34?), with a transition to heavier values in summer (typically -28 to -31?). Using a mixing equation and typical end members for C3 and C4 plants, we found that this is due to relative increases in the contributions from C4 plants in the summer season. Using backward air-mass trajectory analyses, it was shown that the Asian continent was the major source region for C3 plant material during winter/spring, whereas Indonesia/Australia and possibly the Americas were the major source regions for C4 material during the summer/autumn. Also observed was an enhanced atmospheric transport of n-alkanes from C4 plants in 1991 summer/autumn during a strong El Nino event, which was associated with forest and bushfires in Indonesia and Australia. In addition to providing information on contemporary processes, this study also provides a base for future paleoclimatological work in ocean sediments. ? 2005 Elsevier Inc. All rights reserved.
Keywords: AEROSOL; ATMOSPHERIC TRANSPORT; CARBON ISOTOPE; ISOTOPIC COMPOSITION; MARINE ATMOSPHERE; SEASONAL VARIATION; EMBRYOPHYTA